The Analysis of Residues Pesticide in Curly Red Chili and Big Red Chili (Capsicum annum) at Traditional Market of Makassar City - Riski Amaliah; Makmur Selomo; Muhammad Rusmin (HIGIENE: Jurnal Kesehatan Lingkungan, 2015)
Chili (capsicum annuum) is one of the important vegetable crops. Pesticides are remaning levels of residue pesticide after being applicated to crops. In Indonesia pesticide is widely used in agriculture to increase food production. Side effects of pesticide use can cause environmental pollution and leave residues pesticidein agricultural yields. This study aims to determine the content of residues pesticide in curly red chili and big red chili in in 2014 at traditional market of Makassar city. Type of research is descriptive quantitative approach. The sample selection is based on purposive sampling method, the sample criteria of chili is from two major distributors to market, curly red chili and big red fresh chili, chili is not getting any treatment from the distributor. The results of this study indicate the detection of pesticide residues with the active ingredient in red chili big profenofos in the capture of the distributor Pa'baeng-Baeng market and Terong market in 2014 of Makassar city ie <0.1 mg/kg, but still far from the quality standard threshold value of residues pesticide is 0.5 mg/kg. The chili is still considered safe.Keywords: Chili, Residues, Pesticides, Traditonal Market